Pendampingan Perancangan Taman Bermain dan Ruang Terbuka di Desa Sitimulyo - Amos Setiadi; Gerarda Orbita Ida Cahyandari; Hatta Musthafa Adham Putra; Ernesta Uba Wohon (PELITA NUSA TENGGARA, 2026)
Open Spaces are part of urban areas that significantly influence the quality of the city's environment. Open Spaces are part of urban open spaces filled with endemic and introduced plants and vegetation to support ecological, socio-cultural, and architectural benefits, as well as provide economic benefits to the community. Open Spaces are public areas, often in the form of parks, designed to serve residents. These spaces can take the form of green fields equipped with recreational and sports facilities, as well as sports complexes featuring 80% to 90% green areas. All of these facilities are public. This Community Service project utilizes a design concept that combines vegetation layout with perennial trees, shrubs, and bushes planted in groups or scattered throughout the area. Vegetation functions to create a microclimate and acts as a boundary between activities. In addition to the vegetation concept, it also encompasses the arrangement of recreational and sports facilities such as fields, playgrounds, restrooms, seating, and lighting.